Chapter 7 Amazonian Waterway, Amazonian Water-Worlds Rivers in Government Projects and Indigenous Art - Borea, Giuliana (Taylor & Francis, 2020)
This interdisciplinary book brings into dialogue research on how different fluids and bodies of water are mobilised as liquid ecologies in the arts in Latin America and the Caribbean. Examining the visual arts, including multimedia installations, performance, photography and film, the chapters place diverse fluids and systems of flow in art historical, ecocritical and cultural analytical contexts. The book will be of interest to scholars of art history, cultural studies, environmental humanities, blue humanities, ecocriticism, Latin American and Caribbean studies, and island studies.